Public Opinion Monitoring of Sports Stars Based on Text Sentiment Analysis - Yu, Lingfeng (International Journal of Computer Science and Information Technology, 2024)
Traditional methods of monitoring public opinion often rely on questionnaires or ballots, which are not only time-consuming and labour-intensive, but also difficult to reflect public sentiment changes and trends in real time. With the development of machine learning and natural language processing technologies, it has become possible to automatically analyse large-scale text data by algorithms and identify the emotional tendencies therein. In this paper, the analysis and statistics of public opinion are achieved through relevant algorithmic models.